Pengembangan Model Bisnis Dan Strategi Pelayanan Kesehatan XYZ - Ardian surya Nurhakim; Ono Suparno; Dodik Ridho Nurrochmat (School of Business, Bogor Agricultural University (SB-IPB), 2018)
XYZ is a company engaged in the field of health care. Companies that grow and develop require the right business model in order to achieve their visions and missions. One business model that successfully changed the complex business concept to be simple and understandable is the Business Model Canvas (BMC) developed by Alexander Osterwalder and Yves Pigneur. The objectives of this research were to analyze business models of XYZ organization through business model canvas approach, to identify key factors as strengths and weaknesses affecting the operational of XYZ organization, to formulate a strategy design required for the development of XYZ organization. Out of the nine elements of BMC, four elements were selected as top priorities for the company to improve its business strategy i.e. the elements of key activities, customer relationships, customer segments, and revenue streams. The results of BMC also show that the management needs to improve its business model and strategy for future development of XYZ organization e.g. by adding outlets in strategic places, forming a marketing team, as well as holding periodic training of human resources to optimize HR function.Keywords: business model, health care, HR, BMCAbstrak: XYZ merupakan perusahaan yang bergerak di bidang pelayanan kesehatan. Perusahaan yang bertumbuh dan berkembang membutuhkan model bisnis yang tepat guna mencapai visi dan misi perusahaan. Salah satu model bisnis yang berhasil mengubah konsep bisnis yang rumit menjadi sederhana dan mudah dipahami adalah Business Model Canvas (BMC) yang dikembangkan oleh Alexander Osterwalder dan Yves Pigneur. Tujuan dari penelitian ini adalah menganalisa model bisnis organisasi XYZ melalui pendekatan model bisnis kanvas, mengidentifikasi faktor-faktor kunci yang menjadi kekuatan serta kelemahan yang berpengaruh dalam operasional organisasi XYZ, merumuskan rancangan strategi yang diperlukan untuk pengembangan organisasi XYZ. Hasil dari sembilan elemen BMC dipilih empat elemen yang menjadi prioritas utama perusahaan XYZ untuk memperbaiki strategi bisnisnya yaitu pada elemen key activities, customer relationships, customer segments, dan revenue streams. Hasil BMC juga menunjukan bahwa perusahaan perlu melakukan perbaikan model bisnis dan strategi guna pengembangan organisasi XYZ kedepannya, seperti menambah gerai outlet di tempat yang dianggap strategis, membentuk tim marketing, serta melakukan pelatihan SDM secara berkala untuk mengoptimalkan fungsi SDM.Kata kunci: model bisnis, pelayanan kesehatan, SDM, BMC